Analisis Faktor Kebahagiaan pada Mahasiswa Generasi Z - Prafitralia, Anisah (Psychospiritual: Journal of Trends in Islamic Psychological Research, 2023)
Happiness is one of the most common life goals pursued by humans, but the concept of happiness itself remains relatively difficult to understand and scientifically measure. The meaning of happiness can differ between individuals and cultures. Each generation faces different challenges, so the interpretation of happiness can also differ. Understanding happiness can help individuals (in this case, Generation Z students) to achieve greater happiness and well-being in their lives. This study aims to describe the factors that influence happiness among Generation Z students. The research method used was a survey. The researcher collected data from 27 participants who were students of Islamic Guidance and Counseling program. Data was collected through a questionnaire to learn about their perceptions and experiences of happiness and the factors that influence it. The survey was conducted online. The results of the study showed that factors that can bring happiness to Generation Z students include achieving desires/expectations (29.6%), being with loved ones (25.9%), vacation and entertainment (18.5%), being able to make others happy (11.11%), peace of mind (7.4%), and others (7.4%).